Genetically modified whole-cell bioreporters for environmental assessment - Xu, Tingting (Ecol Indic, 2013)
Living whole-cell bioreporters serve as environmental biosentinels that survey their ecosystems for harmful pollutants and chemical toxicants, and in the process act as human and other higher animal proxies to pre-alert for unfavorable, damaging, or toxic conditions. Endowed with bioluminescent, fluorescent, or colorimetric signaling elements, bioreporters can provide a fast, easily measured link to chemical contaminant presence, bioavailability, and toxicity relative to a living system. Though well tested in the confines of the laboratory, real-world applications of bioreporters are limited. In this review, we will consider bioreporter technologies that have evolved from the laboratory towards true environmental applications, and discuss their merits as well as crucial advancements that still require adoption for more widespread utilization. Although the vast majority of environmental monitoring strategies rely upon bioreporters constructed from bacteria, we will also examine environmental biosensing through the use of less conventional eukaryotic-based bioreporters, whose chemical signaling capacity facilitates a more human-relevant link to toxicity and health-related consequences.